Family adaptation and developmental disability - Studman, Lisa Jane (Curtin University, 2014)
This project compared the effects of a family behavioural intervention on measures of family adaptation for parents of children with developmental disabilities. Different structural versions of a Double ABCX model of family adaptation were then tested. Significant, large intervention effects were found for parenting and child behavior, but not for other variables. Structural equation modelling supported a theoretically plausible additive version of the Double ABCX model. Theoretical and applied implications of the research are discussed.